Structural, optical, opto-thermal and thermal properties of ZnS–PVA nanofluids synthesized through a radiolytic approach - Alireza Kharazmi; Nastaran Faraji; Roslina Mat Hussin; Elias Saion; W. Mahmood Mat Yunus; Kasra Behzad (Beilstein Journal of Nanotechnology, 2015)
This work describes a fast, clean and low-cost approach to synthesize ZnS–PVA nanofluids consisting of ZnS nanoparticles homogeneously distributed in a PVA solution. The ZnS nanoparticles were formed by the electrostatic force between zinc and sulfur ions induced by gamma irradiation at a dose range from 10 to 50 kGy. Several experimental characterizations were conducted to investigate the physical and chemical properties of the samples. Fourier transform infrared spectroscopy (FTIR) was used to determine the chemical structure and bonding conditions of the final products, transmission electron microscopy (TEM) for determining the shape morphology and average particle size, powder X-ray diffraction (XRD) for confirming the formation and crystalline structure of ZnS nanoparticles, UV–visible spectroscopy for measuring the electronic absorption characteristics, transient hot wire (THW) and photoacoustic measurements for measuring the thermal conductivity and thermal effusivity of the samples, from which, for the first time, the values of specific heat and thermal diffusivity of the samples were then calculated.